2019
DOI: 10.12688/gatesopenres.13053.1
|View full text |Cite
|
Sign up to set email alerts
|

Group antenatal care versus standard antenatal care and effect on mean gestational age at birth in Rwanda: protocol for a cluster randomized controlled trial

Abstract: Background: Group antenatal care has demonstrated promise as a service delivery model that may result in improved outcomes compared to standard antenatal care in socio-demographic populations at disparately high risk for poor perinatal outcomes. Intrigued by results from the United States showing lower preterm birth rates among high-risk women who participate in group antenatal care, partners working together as the Preterm Birth Initiative - Rwanda designed a trial to assess the impact of group antenatal care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…This study included one primary (group antenatal care) and two secondary (basic obstetric ultrasound and urine pregnancy tests in the community) interventions. These interventions are described below, and more details are available in a separate publication [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study included one primary (group antenatal care) and two secondary (basic obstetric ultrasound and urine pregnancy tests in the community) interventions. These interventions are described below, and more details are available in a separate publication [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…During the second hour of the session, the provider and community health worker co-facilitated a discussion of health-related topics that aligned with the stage of pregnancy and the health issues of highest importance at that time. The full list of visit timing and topics at each visit are described elsewhere [ 17 ]. Providers and community health workers elicited concerns and questions from women and encouraged group care participants to share knowledge and support with one another.…”
Section: Methodsmentioning
confidence: 99%
“…However, the WHO was cautious, because premature adoption of a new model can have serious negative consequences, as exemplified by the reversal of the 4visit model [39]. A growing body of literature shows that group antenatal care is feasible and acceptable in many low and middle-income countries across the globe [40][41][42][43][44][45][46][47][48][49][50]. Additional work is underway in Mali, China, Ethiopia, Surinam, and elsewhere [51].…”
Section: Introductionmentioning
confidence: 99%
“…Additional work is underway in Mali, China, Ethiopia, Surinam, and elsewhere [51]. Most of these studies do not yet have results, but 3 studies in Africa have noted positive outcomes [43,52,53]. A large cluster-randomized trial in Nigeria and Kenya found greater antenatal care attendance in both countries and more birth planning for a facility-based birth in Nigeria [52,53].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation